PEMBERDAYAAN MASYARAKAT DALAM PERSPEKTIF AL QUR’AN - Tomi Hendra, M.Sos (Hikmah, 2017)
Empowerment is an effort to provide power (empowerment) or strengthening (strengthening) to the community. In other words, community empowerment is defined as the ability of individuals with the community in building community empowerment in question. Community empowerment is also interpreted as an attempt to change people's behavior in a better direction, so that the quality and welfare of their lives can gradually increase ". Allah does not change The state of a people so they change the conditions that exist in themselves. and if Allah willed evil for a people, then no one can reject it; and there is no protector for them besides Him. "(Q.S Ar-Ra'd: 11)Community empowerment is an effort done in the form of real activities in the community. Activities that strive to awaken the community in order to use and choose their lives to achieve a better level of living in all aspects. The study in this paper seeks to express the meaning of empowerment and matters related to community empowerment in the perspective of the Qur'an.Keywords: Empowerment, Community, Perspective of The Qur’an